Elevated Levels of Ketopantoate Hydroxymethyltransferase (PanB) Lead to a Physiologically Significant Coenzyme A Elevation in Salmonella enterica Serovar Typhimurium - Rubio, Aileen (American Society for Microbiology, 2002)
Pantothenate is the product of the ATP-dependent condensation of pantoate and β-alanine and is a direct precursor of coenzyme A. A connection exists between pantothenate biosynthesis and thiamine biosynthesis in Salmonella enterica serovar Typhimurium since derivatives of a purF mutant that can grow (on glucose medium) in the absence of thiamine excrete pantothenate. We show here that the causative mutation in three such mutants was the addition of a CG base pair upstream of the panB gene. This base addition brings the spacing between the −10 and −35 hexamers of the promoter to a consensus spacing of 17 bp and results in increased transcription of the pan operon. Furthermore, overexpression of PanB caused by this mutation, or by other means, was necessary and sufficient to increase pantothenate production and allow PurF-independent thiamine synthesis on glucose medium.